Effectiveness and safety of adalimumab to treat outpatient ulcerative colitis: A real-life multicenter, observational study in primary inflammatory bowel disease centers. Issue 34 (August 2018) - Tursi, Antonio; Elisei, Walter; Faggiani, Roberto; Allegretta, Leonardo; Valle, Nicola Della; Forti, Giacomo; Franceschi, Marilisa; Ferronato, Antonio; Gallina, Sara; Larussa, Tiziana; Luzza, Francesco; Lorenzetti, Roberto; et al.
Abstract : Abstract: Adalimumab (ADA) was approved in Italy for the treatment of ulcerative colitis (UC) unresponsive to standard treatments in 2014, but no data from real life are currently available. The aim of the present study was to assess the real-life efficacy and safety of ADA in managing UC outpatients in some Italian primary inflammatory bowel disease (IBD) centers after approval of ADA reimbursement. Consecutive UC outpatients with at least 3-month follow-up were retrospectively evaluated. The primary end point was the induction and maintenance of remission in UC, defined as Mayo score ⩽2. One hundred seven patients were included. At 3-month follow-up, obtained in 102 (95.3%) patients, 56 (54.9%) patients achieved a clinical remission. At univariate analysis, both Mayo partial score >7 and Mayo subscore for endoscopy = 3 at entry showed to be significantly associated with the lack of remission induction. During a median (95% confidence interval [CI]) follow-up of 18 (12–24) months, 56.6% of patients were under clinical remission; clinical response was achieved in 89.2% of cases. Mucosal healing was achieved in 66 (76.7%) patients, and colectomy occurred in 3 (2.8%) patients. Both C-reactive protein and fecal calprotectin values significantly decreased during follow-up. Steroids discontinuation occurred in 67 (66.7%) patients, and ADA dose escalation was adopted in 9 (16.1%) patients under remission. No factor was significantly related to the maintenance of clinical remission. This first Italian experience found ADA safe and effective to induce and maintain remission in real-life UC outpatients.